Peran dan Strategi Implementasi E-Learning dalam Pembelajaran di Indonesia: Sebuah Studi Literatur : [The Role and Strategy of E-Learning Implementation in Learning in Indonesia: A Literature Study] - Yehory Yoshy Mustakim; Agustina Dwi Ayu Permatasari; Mathias Marciano Manurung; Yosephina Sianti Djeer (Universitas Pelita Harapan, 2025)
Technological developments have greatly affected the dimensions of life and education, one of which is the use of e-learning in learning which is considered to be able to answer the learning needs of the 21st century. However, there are many obstacles faced, such as regulations, human resources, infrastructure, and limited budgets that should be a serious concern for various parties, especially governments and education providers. This research aims to explore the impact of the use of e-learning in learning in Indonesia, what are the challenges, and how efforts must be made by the government and education providers in order to implement e-learning in learning and how to overcome the challenges. This study uses a qualitative method with a literature study approach. The results of this study show that e-learning brings major changes to education in Indonesia, but it has challenges such as regulations that have not accommodated the integration of e-learning in learning, human resources that are not optimal, the availability of inadequate facilities and infrastructure, and a limited budget. To overcome these challenges, the researcher concluded and provided advice to the government and education providers to prepare adequate regulations, human resources, facilities and infrastructure, and budgets so that in their implementation, e-learning can accommodate the needs of diverse communities.